Turning a Blind Eye to African Refugees and Immigrants in a Tourist City: A Case-study of Blame-shifting in Cape Town - Ruiters, Greg; Lombard, Felicia; Uwimpuhwe, Denys (African Human Mobility Review, 2021)
What role do municipalities play in limiting xenophobia in all its forms and what should these bodies do in promoting the integration of African immigrants? This paper analyzes a case study of Cape Town’s policies and programs concerning African immigrants and refugees following the 2008 xenophobic crisis, up to 2016. Municipalities as a separate sphere of the government have their own space to address socio-political problems and to shape local alliances and urban life. Despite being a tourist-led, gentrifying city which substantially draws on vulnerable African immigrant labor, Cape Town’s leaders and businesses, however, have no explicit policies or programs to address xenophobia – a ticking time bomb; and they tend to shift the blame to other actors. City leaders and employers see African immigrants in an instrumental way (as mere labor; a financial burden and not as potential citizens). This paper focuses on local government’s definition of the ‘foreign immigrant problem’ and its poor record of reducing the drivers of xenophobic conflicts in South African cities, recognizing that while cities are not the only players, they certainly are the closest to the problem. The paper concludes that the city needs a proactive, comprehensive approach, recognizing migrants and their organizations, especially foreign workers, legal immigrants and refugees, as key city builders, stakeholders and potential citizens in the city. The paper draws on interviews with city officials, migrants and asylum seekers in the City of Cape Town.